Clarification of the Cut-off Score for Nine-Item Internet Gaming Disorder Scale–Short Form (IGDS9-SF) in a Chinese Context - Qin, Lixia; Cheng, Limei; Hu, Maorong; Liu, Qiaosheng; Tong, Jianqin; Hao, Wei; Luo, Tao; Liao, Yanhui (Frontiers in Psychiatry, 2020)
Background: The nine-item Internet Gaming Disorder Scale–Short-Form (IGDS-SF9) is a self-reported screening measure based on the Diagnostic and Statistical Manual of Mental Disorders (DSM-5) criteria. It has been used to assesses symptoms and prevalence of Internet Gaming Disorder (IGD) in general population. Despite its widespread use, confusion arising from the recommended cut-off score for a positive diagnosis. This study aimed to identify the appropriate cut-off score for IGDS-SF9 in the context of Chinese. Methods: The present study included a sample from clinical settings (n=131) and another from universities (n=3742). IGDS-SF9 measurement and structured clinical interviews based on DSM-5 criteria for IGD were conducted in the sample from clinical settings. The cut-off score was determined using the Receiver Operating Characteristics (ROC curve). The validity of this cut-off score was further assessed in a sample from universities. Results: Mathematical models suggest that the score of 32 is the optimal cut-off point (Youden’s index: 96.2%, diagnostic accuracy: 96.1%, sensitivity: 98.0%, speciﬁcity: 91.9%, NPV: 91.9%, and NPY is 100%). The prevalence of IGD is 2.9% in this study. Conclusion: This study suggested that the optimal cut-off score of IGDS-SF9 is 32 for the positive diagnosis of IGD in the context of Chinese.